Detection of Rifted Continental Margin from Satellite Gravity Data - Nasar Mohamed Elzawam (Journal of Pure & Applied Sciences, 2017)
The principle to understand of plate tectonics is presumably which so-called rifted continental margins formation. To determine the structure and formation processes of the rifted margins, recent observation of mantle exhume has been observed which associated with the production of anomalies thin ocean crust- depth dependent lithosphere extension at rifted margin has revolutionized our knowledge of structure and process that form rifted margin. The new quantitive of satellite gravity data will be used to emphasis this idea. Recent finite element modeling of formation of passive rifted margins suggests that differentially stretching occurs during early sea-floor spreading generating transitional continental oceanic boundary, exposing continental mantle material at the surface. Its documented along present day and ancient passive continental margins where it occurred during the final rifting stage during break-up of the continental lithosphere. The key to understanding mantle exhumation at ocean ridges is the coupling of fault exhumation and the production of thin ocean crust at slow spreading ridges.